Recent Engineering Applications for Noise Reduction in an Automotive Industry - Berkay Uğur; Ender Pak; Ülge Taş (Journal of Advanced Research in Natural and Applied Sciences)
Industrialization harms as it results in the emission of noise into the surroundings and employees. Especially noise is one of the most common causes of hearing disorders and one of the most common occupational diseases in the industry. Reducing the main noise sources has become increasingly urgent since the effect on employee health was negative. Although noise reduction is an important issue in the industry, previous research has not addressed it adequately, particularly in the automotive industry. This paper presented a detailed case study on the reduction of noise in a pilot area of an automotive assembly line. The paper aimed to improve the quality of the working environment by reducing the use of Personal Protective Equipment (PPE) and noise reduction. For this purpose, noise measure tools were used: a Svantec-type noise dosimeter and a sound level meter. In the course of studies, it was creating noise maps (before/after), in order to verify whether the proposed measures will be sufficient. Once the proposed measures have been implemented, a 14.2% reduction in noise levels helped ensure employees’ safety by reducing the need for mandatory PPE. Meanwhile, the noise reduction percentage for AGV is the highest among the five noise sources, at 20.9%. Results showed that the sound pressure levels dropped from 110 dBA to 87 dBA and reduced on average for AGV. Reducing reliance on PPE and implementing noise reduction measures enhances pilot area safety and contributes to a more ergonomic and sustainable work environment. The implementation of this case, the application of the suggested measures, and the subsequent verification approved a considerable reduction in the noise levels in the influenced pilot area, and the measures applied were assessed as highly effective with result rates.